2019
DOI: 10.3382/ps/pey564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manganese preconditioning and replacing inorganic manganese with organic manganese on performance of male broiler chicks

Abstract: The effects of manganese (Mn) preconditioning, 96 h post-hatch followed by the replacement of inorganic Mn with different levels of organic Mn (5 to 21 D), on growth, tissue excreta Mn content, gene expression, and enzyme activity were evaluated. A total of 420 day-old male Cobb 500 broilers were divided into 2 groups. One group was fed a corn–soybean meal basal diet containing 17 mg of Mn/kg (preconditioning diet, MnPD); the second group was fed the non-preconditioning diet (NPCD), which was the MnPD suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…As an essential trace element, manganese (Mn) is a component or activator of many essential enzymes, such as arginase, pyruvate carboxylase, hydrolases, etc., which are involved in carbohydrate, lipid, and protein metabolism and many crucial biochemical reactions [1,2]. It is also an essential cofactor of chondroitin sulfate synthesis that is closely related to the bone formation of broilers [3]. Otherwise, Mn plays a vital role in antioxidant Animals 2021, 11, 3470 2 of 13 and immune systems of animals [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As an essential trace element, manganese (Mn) is a component or activator of many essential enzymes, such as arginase, pyruvate carboxylase, hydrolases, etc., which are involved in carbohydrate, lipid, and protein metabolism and many crucial biochemical reactions [1,2]. It is also an essential cofactor of chondroitin sulfate synthesis that is closely related to the bone formation of broilers [3]. Otherwise, Mn plays a vital role in antioxidant Animals 2021, 11, 3470 2 of 13 and immune systems of animals [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Olgun(2017) stated that the dietary addition of 90 mg Mn/kg feed prevented various disorders such as perosis, maintained normal development of broilers and improved egg shell quality parameters of laying hens. The supplementation of 12 mg Mn/kg feed from both sources (inorganic or organic) was sufficient to provide optimum broiler performance(Mwangi et al 2019). Thus, Mn in poultry nutrition is crucial due to its role in egg shell and bone development and metabolism of nutrients.…”
mentioning
confidence: 99%
“…The results of another study (Mwangi et al, 2019) confirmed that feeding broiler chickens with a slight deficiency of manganese in the diet affects the growth rate and the concentration of this element in tissues. The addition of 75-100 mg/kg manganese to the main corn-soy diet increases overall resistance and reduces the fat deposition in broiler chickens (Ghosh et al, 2016).…”
Section: Discussionmentioning
confidence: 73%